AN ANALYSIS OF THE TRANSLATION TECHNIQUE USED BY STUDENT IN TRANSLATING POETRY TEXT ENTITLED “EQUIPMENT’ BY EDGAR ALBERT GUEST - Virga Putra Darma; Salsabila Nuravianti (Program Studi Pendidikan Bahasa Inggris Institut Pendidikan dan Bahasa Invada, 2023)
This is a qualitative research with discourse analysis methodes as a research design. The data that is used in qualitative research come from a range of collection methods. The reason for using a qualitative method is because qualitative research is more all encompassing since it includes information from numerous sources to pick up a more profound understanding from a person counting viewpoints and states of mind (Nassaji, 2015). This study aims to analyze translation technique used by students in poetry text Entitled “Equipment” by Edgar Albert Guest. In accordance with the research title related to translation techniques, the researcher will analyze the translation technique in the text of the poetry by Edgar Albert guest with the title